Protein S-nitrosylation in plants under abiotic stress: an overview - Romero-Puertas, María C.; Rodríguez-Serrano, María; Sandalio, Luisa M. (Frontiers in Plant Science, 2013)
Abiotic stress is one of the main problems affecting agricultural losses, and understanding the mechanisms behind plant tolerance and stress response will help us to develop new means of strengthening fruitful agronomy. The mechanisms of plant stress response are complex. Data obtained by experimental procedures are sometimes contradictory, depending on the species, strength and timing applied. In recent years NO has been identified as a key signalling molecule involved in most plant responses to abiotic stress, either indirectly through gene activation or interaction with reactive oxygen species and hormones; or else directly, as a result of modifying enzyme activities mainly by nitration and S-nitrosylation. While the functional relevance of the S-nitrosylation of certain proteins has been assessed in response to biotic stress, it has yet to be characterized under abiotic stress. Here, we review initial works about S-nitrosylation in response to abiotic stress to conclude with a brief overview, and discuss further perspectives to obtain a clear outlook of the relevance of S-nitrosylation in plant response to abiotic stress.